Kajian Penggunaan Karbon Aktif Kulit Singkong Untuk Meningkatkan Kinerja Proses Koagulasi Dan Flokulasi Dalam Pengolahan Air - Viena, Winda Carla; Wikaningrum, Temmy (Baselang, 2024)
Based on statistical measures of food consumption in 2022, the annual quantity of cassava waste amounts to 578 tons. Beyond its usage as animal feed, cassava skin has further potential as an active carbon source for absorbing heavy metals. This is because cassava skin contains carbon (59.31%), cellulose (13.75%), and lignin (9.14%), which may serve as precursors in the production of activated carbon. The objective of this work is to identify the optimal use of cassava skin waste. This study used a laboratory-based approach, beginning with the production of activated carbon from cassava peel and then applying it to synthetic materials on a laboratory scale. A cassava peel activated carbon produced using an H3PO4 activator has been determined to satisfy the requirements specified in the SNI 06-3730-1995 standard. The activated carbon has a water content of 0.65%, an ash content of 0.85%, a pure carbon content of 98.72%, and an iodine absorption capacity of 809 mg/g. Based on the findings of this experiment, it can be inferred that including a processing unit prior to the aforementioned stage, such as flash mixing and sedimentation, is necessary to optimize the efficiency of activated carbon technology. Based on the test result, 2.5 gr of activated carbon added to 700 ml of sample was continued with the addition of PAC 30 mg/l. Able to reduce turbidity level with a removal efficiency of up to 89.9%, iron of 43%, and ammonia at 17% these results are better than the use of PAC without activated carbon. The adsorption isotherm model represents the adsorption of iron and ammonia is Freundlich while turbidity is Langmuir.